CHARACTERISTICS OF STRAWBERRY (Fragaria x anassa) AND MANALAGI APPLE (Malus sylvestris) BEVERAGE POWDER AS AFFECTED BY ENCAPSULANT TYPE AND CONCENTRATION - Adhwa Nurulalifah; Nuzlan Rasjid; Willy Pranata Widjaja; Yudi Garnida (Department of Food Technology, Universitas Pasundan, Bandung, 2026)
Encapsulation plays a crucial role in protecting phenolic compounds, which are abundant in strawberry (Fragaria ananassa) and Manalagi apple (Malus sylvestris), two fruits commonly used in powdered beverage formulations due to their high antioxidant activity. This study aimed to evaluate the effects of encapsulant type, concentration, and their interaction on the characteristics of strawberry and Manalagi apple powder drinks. A 3×3 factorial experiment was conducted using a randomized block design (RBD) with two factors: encapsulant type (maltodextrin, maltodextrin + alginate, and maltodextrin + chitosan) and encapsulant concentration (20%, 25%, and 30%), each replicated three times for a total of 27 experimental units. Freeze drying was employed as the drying method. The study assessed chemical responses (total polyphenols, total flavonoids, antioxidant capacity), physical response (solubility time), and organoleptic properties (taste, aroma, and color). Results demonstrated that both encapsulant type and concentration, as well as their interaction, significantly affected the chemical and physical responses but did not influence the organoleptic attributes. In silico toxicity analysis revealed moderate risks, including potential mutagenic, carcinogenic, and hepatotoxic effects, along with the ability of the compounds to cross the blood–brain barrier. Nevertheless, the compounds also showed beneficial biological activities, such as antioxidant, gastroprotective, and anti-ulcerative properties, suggesting potential therapeutic applications. Keywords: powder drink, encapsulant, strawberry, manalagi apple